2020
DOI: 10.1021/acsanm.0c00117
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Graphene-Based Platforms for Dual Biorecognition of Molecules

Abstract: Expanding the single molecule detection, enabled by laserinduced graphene (LIG) technology, for portable and on-site analysis, a dual molecule system with a two-working-electrode architecture was developed for ascorbic acid (AA) and amoxicillin (AMOX) detection, which are currently used in aquaculture and persist as water contaminants. The biorecognition element of each target compound was a suitable molecularly imprinted polymer (MIP). The AMOX MIP was developed herein for the first time and assembled by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…Marques’s group fabricated a sensor for amoxicillin and ascorbic acid using molecularly imprinted polymers ( Figure 6 a). 88 With this technique, polymerization is performed in the presence of the analyte: their interaction during polymerization and the successive washing create cavities that grant the polymer an affinity for the analyte. In their fabrication process, different procedures were used to treat LIG electrodes and make them sensitive to amoxillicin or ascorbic acid.…”
Section: Functionalization Of Lig Electrodes For Selective Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marques’s group fabricated a sensor for amoxicillin and ascorbic acid using molecularly imprinted polymers ( Figure 6 a). 88 With this technique, polymerization is performed in the presence of the analyte: their interaction during polymerization and the successive washing create cavities that grant the polymer an affinity for the analyte. In their fabrication process, different procedures were used to treat LIG electrodes and make them sensitive to amoxillicin or ascorbic acid.…”
Section: Functionalization Of Lig Electrodes For Selective Analysesmentioning
confidence: 99%
“… Illustrative LIG sensors with polymer coating: (a) LIG sensor fog amoxicillin and ascorbic acid using molecularly imprinted polymers,[Panel (a) was adapted with permission from ref ( 88 ). Copyright 2020, American Chemical Society, Washington, DC; adapted with permission from, 90 Copyright 2020 American Chemical Society c) LIG electrodes using EBT for detb) flexible LIG pH sensor using polyaniline,ecting chloramphenicol, a pollutant antibiotic, adapted from, 89 Copyright 2019, Elsevier.…”
Section: Functionalization Of Lig Electrodes For Selective Analysesmentioning
confidence: 99%
“…In contrast to semiselective electronic tongue systems, surface modifications have also been explored to endow the pristine LIG with highly selective detections toward specific biochemicals and even bacteria. Functional groups usually involve antibodies, enzymes, aptamers, and molecularly imprinted polymers [83,[96][97][98][99][100][101]. For example, Soares et al have reported LIG-based electrochemical immunosensors for detections of Salmonella enterica, as schematically illustrated in Fig.…”
Section: Biofluids Biochemical Sensorsmentioning
confidence: 99%
“…For example, oxide semiconducting inks usually need the assistance of laser annealing to improve the electronic or mechanical performances. [25][26][27] As for organic semiconducting inks, their crystallization heterogeneity is still a challenging issue for fabricating complex electronic structures and devices with high-resolution featured patterns and highly electrical performance by layer-by-layer fashion. Moreover, the compatibility between printable active components and printing techniques is often established at the cost of sacrificing device performance, thus limiting the feasibility in a wide variety of highly integrated electronics and devices.…”
Section: Introductionmentioning
confidence: 99%